ALUMNI DATA PROCESSING APPLICATIONS STMIK JAKARTA STI & K USING MICROSOFT VISUAL FoxPro 9.0 - Doni R. Djafar; Yudi Irawan Chandra (Jurnal Sistem Informasi, 2009)
Abstract :This explains the scientific writing about the Application of Data Processing Alumni JAKARTA STMIK STI & K by using Microsoft Visual FoxPro 9.0. Where an existing application has a menu that has not been integrated and enhanced by the author with this application. The data in this application obtained through a form that is spread by the Institute of Development Computerization (LPK) JAKARTA STMIK STI & K section Career Services Center (Carreer Center) to alumni. Alumni who referred to here are students who Three have passed the Diploma session or Strata One. In this application, alumni data that has not worked can be processed into a file Microsoft Office Excel, where the files are requested by the company Three graduate diploma requires a person or Strata One with various criteria are needed so that graduates can obtain employment information. Ultimately Applications of Data Processing Alumni STMIK JAKARTA STI & K This will be applied on Computerization Development Institute (LPK) STMIK JAKARTA STI & K the Career Services Center (Carreer Center) to accommodate alumni data and simplify the service vacancies informationjobs for alumni.